Implementasi Kebijakan Layanan Penitipan Barang dan Video Call Sebagai Pengganti Layanan Kunjungan.Pada.Masa.Pandemi. Covid-19.. di Lembaga Pemasyarakatan Kelas IIB. Kayu Agung - Lisdiana, Lisdiana; Hestirinaih, Deby Chintia; Purnama, Reza Meidiansyah (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2022)
The existence of goods storage services as a substitute for visiting services during the Covid-19 pandemic certainly has a positive impact on prisoners and convicts, namely to prevent and break the chain of spread of Corona Virus Disease (Covid-19) in the implementation of Correctional Duties and Functions at the Correctional Technical Implementing Unit. effectively. The procedures for safekeeping of goods include: Mandatory to have an identity card, Dress and be polite, Wear a mask, Everyone is only allowed to bring 1x deposit for correctional inmates, Forbidden to bring excessive deposited goods and Forbidden to bring items that are not allowed by the officer . The purpose of this study was to analyze the Implementation of the Goods Custody Service and video call Policy as a Substitute for Visiting Services during the Covid-19 Pandemic Period at the Kayu Agung Class IIB Correctional Institution. The problem in the research is the lack of human resources for the storage of goods and the lack of goods storage infrastructure, namely X-Ray tools because so far the storage of goods is still manual. The data analysis technique used in this research is qualitative data analysis technique. This study concludes that the overall implementation of the Goods Custody Service and video call Policy as a Substitute for Visiting Services During the Covid-19 Pandemic Period at the Class IIB Kayu Agung Penitentiary has been carried out properly, although in its implementation there are still obstacles/constraints such as the lack of human resources in the section Storage of goods and video call and goods storage infrastructure is still lacking, namely X-Ray tools because so far the storage of goods is still manual.